Nur77 improves ovarian function in reproductive aging mice by activating mitophagy and inhibiting apoptosis - Ying Yao; Bin Wang; Kaihua Yu; Ji Song; Liyan Wang; Xuehong Zhang; Yulan Li (BMC, 2024)
Abstract Reproductive aging not only affects the fertility and physical and mental health of women but also accelerates the aging process of other organs. There is an urgent need newfor novel mechanisms, targets, and drugs to break the vicious cycle of mitochondrial dysfunction, redox imbalance, and germ cell apoptosis associated with ovarian aging. Autophagy, recognized as a longevity mechanism, has recently become a focal point in anti-aging research. Although mitophagy is a type of autophagy, its role and regulatory mechanisms in ovarian aging, particularly in age-related ovarian function decline, remain unclear. Nerve growth factor inducible gene B (Nur77) is an early response gene that can be stimulated by oxidative stress, DNA damage, metabolism, and inflammation. Recent evidence recommends that decreased expression of Nur77 is associated with age-related myocardial fibrosis, renal dysfunction, and Parkinson's disease; however, its association with ovarian aging has not been studied yet. We herein identified Nur77 as a regulator of germ cell senescence, apoptosis, and mitophagy and found that overexpression of Nur77 can activate mitophagy, improve oxidative stress, reduce apoptosis, and ultimately enhance ovarian reserve in aged mice ovaries. Furthermore, we discovered an association between Nur77 and the AKT pathway through String and molecular docking analyses. Experimental confirmation revealed that the AKT/mTOR signaling pathway is involved in the regulation of Nur77 in ovarian function. In conclusion, our results suggest Nur77 as a promising target for preventing and treating ovarian function decline related to reproductive aging.